Channel Estimation and Equalization Methods for ZP-OFDM under Highly Mobile Environments - Tanangsanakool, Saha; Reangsuntea, Pongsathorn; Mori, Kazuo; Boonsrimuang, Pisit (My University, 2019)
Zero-Padded OFDM (ZP-OFDM) has been attracted a lot of attention as an efficient technique to improve the performance in severe multipath fading channels. Many works were devoted to the equalization method for ZP-OFDM in quasi-static channel model. However, an inter-carrier interference (ICI) which occurred under highly mobile environments would be destroyed orthogonality among subcarriers and causes the degradation of bit error rate (BER) performance due to the time domain channel impulse responses (CIRs) are assumed to be constant over one OFDM symbol. The time domain equalization (TDE) method in conjunction with a time domain CIR estimation method is proposed to solve this problem for the ZP-OFDM signal in the time domain. The advantage of the proposed method is to apply a training sequence (TS) instead of using ZP which enables for estimation of CIR. And also to reduce computational complexity, the proposed method is employed time domain equalization based on the minimum mean squared error (MMSE-TDE) instead of using the conventional frequency domain equalization based on MMSE (MMSE-FDE) method. This paper presents various simulation results under highly mobile environments to demonstrate the effectiveness of proposed TDE method as compared with conventional demodulation methods.
Keywords: ICI; MMSE-FDE; MMSE-TDE; Training sequence (TS); ZP-OFDM